Implementasi Model Pembelajaran STAD untuk Meningkatkan Hasil Belajar Matematika Operasi Hitung Pecahan Pada Siswa Sekolah Dasar di Kabupaten Pulau Morotai - subhan uban hayun; Nurhani Mahmud (Peneliti.net, 2019)
The purpose of this research on the implementation of the STAD type cooperative learning model is that it can improve learning outcomes in Mathematics operations calculate the addition of mixed fractions to elementary school students in Pulau Morotai Regency. Based on data analysis and discussion, the conclusion that can be drawn from this study is the STAD type cooperative learning model can improve student learning outcomes about the addition of mixed fraction operations can be accelerated is not the same as the SD Inpres Sopi elementary school. This was evidenced by an increase in student learning outcomes from the first cycle the value of learning completeness was 35% while in the second cycle the value of mastery learning 90% increased in accordance with KKM (70) which was agreed by the class teacher.